Предмет: Математика,
автор: shvetsov464
Преобразовать √(22+6√(3+√(13+√(48)))).
Ответы
Автор ответа:
1
Ответ:
1 + 3√3
Пошаговое объяснение:
√(22+6√(3+√(13+√(48)))) = √(22+6√(3+√(13+4√3))) = √(22+6√(3+√(1+2√3)²)) =
= √(22+6√(3+1+2√3)) = √(22+6√(4+2√3)) = √(22+6√(1+√3)²) =
=√(22+6(1+√3)) = √(22+6+6√3) = √(28 + 6√3) = √(1+3√3)² = 1 + 3√3
Похожие вопросы
Предмет: История,
автор: dddddd2819
Предмет: Химия,
автор: veronikataradajko
Предмет: Математика,
автор: arinasagala00
Предмет: Математика,
автор: viktoriya116
Предмет: Математика,
автор: oly2183